The move towards a specific tortious civil liability for intelligent robots - bouterfas, Hafida (The journal of Teacher Researcher of Legal and political Studies, 2025)
Owing to the distinctive capabilities of intelligent robots, supported by artificial intelligence, which enable them to engage in self-learning and perform tasks and functions autonomously without human intervention, damages may arise affecting third parties. This, in turn, places the legal framework of civil liability before a complex challenge with regard to ensuring compensation for victims of such acts committed by robots. As a solution, the European Union introduced specific regulations governing robots on 16 February 2017, under which the European legislator adopted the principle of the “human proxy.” This principle assigns legal liability to such a proxy, whether the manufacturer, owner, or user for damages arising from the actions of robots. The primary aim of this study is to examine and analyze the legal framework of this principle as established by the European legislator, with a view to clarifying the mechanism